Bromine‐Promoted Glycosidation of Conformationally Superarmed Thioglycosides. Issue 51 (20th August 2019) - Panza, Matteo; Civera, Monica; Yasomanee, Jagodige P.; Belvisi, Laura; Demchenko, Alexei V.
Abstract: Presented herein is a study of the conformation and reactivity of highly reactive thioglycoside donors. The structural studies have been conducted using NMR spectroscopy and computational methods. The reactivity of these donors has been investigated in bromine‐promoted glycosylations of aliphatic and sugar alcohols. Swift reaction times, high yields, and respectable 1, 2‐ cis stereoselectivity were observed in a majority of these glycosylations. Abstract : Super sugars ! Bromine‐promoted glycosylation of aliphatic and sugar alcohols using highly reactive thioglycoside donors was studied. Swift reaction times, high yields, and respectable 1, 2‐ cis stereoselectivity were observed in a majority of these glycosylations.